PTSD Symptoms and Dementia in Older Veterans Who are Living in Long-Term Care. (February 2022) - Ritchie, Kim; Cramm, Heidi; Aiken, Alice; Donnelly, Catherine; Goldie, Catherine
Co-occurring posttraumatic stress disorder symptoms and dementia can result in increased symptoms, such as suspicion, aggression, and nightmares in Veterans that can be difficult to manage in long-term care environments. The objective of the study was to explore how the co-occurrence of posttraumatic stress disorder symptoms and dementia are understood in Canadian Veterans who are living in long-term care. A descriptive multiple case study was conducted in two Veteran long-term care facilities in Canada. Data collection consisted of semi-structured interviews with Veterans, their family caregivers, and health care providers, non-participant observation, and a chart audit. Three major themes emerged relating to symptom expression and care approach: a) symptoms are the same but different; b) differences in the complexity of care; and c) added dimensions involved in care. The results of this study contribute foundational information about co-occurring posttraumatic and dementia symptoms that can inform policy, care approaches, and potential interventions.